PLANT GENETIC RESOURCES AND THEIR USE IN TRADITIONAL MEDICINE OF BOSNIA AND HERZEGOVINA (W. BALKAN, SE EUROPE) - Redzic, S. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Plant genetic resources (PGR) have long been used in traditional phyto-therapy throughout the Balkan Peninsula [1, 2]. PGR use in human phyto-therapy originated from Asia, Northern Africa, Southern and Northern America. They spread to this region through different dynamic processes of anthrop-genesis and ethno-genesis of nations in this area. Previous research showed specific models of use of certain plants [2]. Ethno – botanical interviews of 145 persons (between 45 – 87 years of age) in more than 10 locations in Bosnia and Herzegovina revealed that 145 of cultivated species are used for different purposes in traditional phyto-therapy. Of these, 55 species are used in the Mediterranean and sub-Mediterranean region while only 19 species are used in the mountainous region (>1,500 m above sea). The majority of the species belong to the following families: Brassicaceae, Poaceae, Rosaceae, Fabaceae, Chenopodiaceae and Asteraceae. All plant parts (spines, leaves, fruits, flowers, seeds, rhizomes) are used in the form of infusions (35%), decoctions (25%), “mazzerati” (15%), tinctures (20%), oils, lotions and others (5%). These preparations are used in the treatment of a wide range of mostly chronic diseases such as stomach problems (30%), respiratory diseases (32%), bones and muscle diseases (18%), heart diseases, diabetes, as tranquilizers, treatment of snake and dog bites. The most widely used species are Abutilon theophrasti, Tropaeolum majus, Balsamita major, Ruta graveolens and Avena sativa. References: 1. Redzic SS (2007) Coll. Antropol. 31: 869-890 2. Redzic S (2007) Planta Med. 73: 1013. 3. Redzic SJ (2006) Ecol. Food & Nutr. 45: 189-232.